The Impact of Radicalism on the Nation's Disintegration - Susi Susi; Echa Surya Surya Nanda Kurniawan; Ended Permadi; Handrian Wibianika; Bibit Wahyu Eriyanto (International Journal of Nusantara Islam, 2021)
The threat of radicalism in the Pancasila state has become an important issue in Indonesia, various research and studies on the phenomenon of the development of radicalism against the disintegration of the nation. The radicalism movement as an ideology is not always marked by acts of violence, but can also be limited to an ideology that does not use violent means. The research method uses a qualitative approach, the analysis is carried out using a qualitative analysis method with descriptive decomposition. In this study, the author only describes and sees the condition of the object of research and analyzes by comparison or comparison of various books, articles, journals and data relating to the impact of radicalism on the disintegration of the nation. The results of the research show that the disintegration of the nation is a serious problem for the nation and state. Disintegration can trigger various conflicts that are even bigger and do not even rule out the possibility of giving birth to a new nation. Radicalism can be suppressed by bringing up an attitude of nationalism.